E-Budgeting ATK pada Badan Pengelolaan Keuangan dan Aset Daerah Kabupaten Gianyar - I Gusti Ayu Jasmiari; Wayan Gede Suka Parwita; Ni Putu Suci Meinarni (Badan Riset dan Inovasi Daerah Provinsi Bali, 2019)
Financial Management and District Asset Agency of Gianyar District is an official government agent of Gianyar District that has the authority to execute the district autonomy in terms of income, financial management, and asset administration. The agency has faced the difficulties in budgeting process of stationary which is not transparent, that will be lead to misappropriation of the budget and there is no clear and detail of the budget of the stationary. This condition will cause inefficient of budgeting for the stationary. The purpose of this research is to build an e-budgeting of stationary on Financial Management and District Asset Agency of Gianyar District that has the correlation with budgeting plan of stationary where a system can be used to manage the budget of the stationary in terms of additional transaction or deduction of stationary. In this research, there are four methods used, those are interview, observation, documentation and literary research. The design of the system is done by analyzing the needs system and was designed by using Data Flow Diagram (DFD) in order to design system and data flow. In this design, the system has been made and a trial of functional system has been done by using Blackbox Testing Method using 24 scenario of trial system, which from that trial showed can be concluded that the system was done appropriately based on the design system.